A Drosophila melanogaster mitotype may have an adaptive meaning - D. V. Petrovskii; L. P. Zakharenko (Вавиловский журнал генетики и селекции)
Several different mitochondrial clades have been found in natural populations of Drosophila melanogaster. Most often, the difference is in single nucleotide substitutions, some of which are conservative. Some clades are rare, and others dominate. It has been reported that clade III dominates over clades V and VI in seven populations of D. melanogaster. We compared D. melanogaster strains with different mitotypes by locomotor activity (using TriKinetics Drosophila Activity Monitor), energy expenditure (by indirect calorimetry, based on measuring oxygen consumption) and life span (under extreme conditions at 29 °C). The nuclear genomes of these strains were aligned for several generations by backcrosses. According to our data, individuals with the mitotype from clade III had a higher level of locomotor activity and longer life span. In terms of energy expenditure, the strains studied did not differ. However, the same level of energy expenditure may be differently distributed between the state of activity and the state of rest or sleep. If the energy expenditure during the sleep in flies with different locomotor activity is the same, then an individual with the same overall energy expenditure can move a greater distance or be active longer. This can be interpreted as an advantage of the strain with the mitotype from clade III compared to the other two mitotypes studied. If individuals have different energy expenditure values at rest, the strains with lower energy expenditure at rest spend less energy during forced inactivity. In this case, the mitotype from clade III should also be advantageous. What nucleotide substitutions in the mitotype from clade III can provide an adaptive advantage is not clear yet. We assume that individuals with widespread clade М(III) may have adaptive advantages compared to other mitotypes due to their greater locomotor activity even with the same energy expenditure. Further studies are required, for mitotypes are polymorphic for single nucleotide polymorphism not only between but also within the clades.